A Quadrennial Review of the National Nanotechnology Initiative: Nanoscience, Applications, and Commercialization - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
Global advances in medicine, food, water, energy, microelectronics, communications, defense, and other important sectors of the economy are increasingly driven by discoveries in nanoscience and the development of nanotechnologies. Engaging the nanoscience and technology community in the crafting of national priorities, developing novel approaches for translating fundamental discovery to a technology readiness level appropriate for venture\/industry funding, increasing domestic student interest in nanoscience to expand the workforce pipeline, and exploring new ways of coordinating the work of the National Nanotechnology Initiative (NNI) are all imperatives if the United States is to fully reap the societal benefits of nanotechnology. A Quadrennial Review of the National Nanotechnology Initiative provides a framework for a redesign of the NNI and its coordination with the goal of achieving a U.S. resurgence in nanotechnology. This report makes recommendations to improve the value of the NNI's research and development strategy and portfolio to the economic prosperity and national security of the United States.

Chemical Laboratory Safety and Security: A Guide to Developing Standard Operating Procedures - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
The U.S. Department of State charged the Academies with the task of producing a protocol for development of standard operating procedures (SOPs) that would serve as a complement to the Chemical Laboratory Safety and Security: A Guide to Prudent Chemical Management and be included with the other materials in the 2010 toolkit. To accomplish this task, a committee with experience and knowledge in good chemical safety and security practices in academic and industrial laboratories with awareness of international standards and regulations was formed. The hope is that this toolkit expansion product will enhance the use of the previous reference book and the accompanying toolkit, especially in developing countries where safety resources are scarce and experience of operators and end-users may be limited.

Review of Proposals for Research on Statistical Methodologies for Assessing Variables in Eyewitness Performance - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
Recognizing the importance of eyewitness identifications in courts of law and motivated by data showing that at least one erroneous eyewitness identification was associated with almost 75% of cases where defendants were later exonerated by DNA evidence, in 2013 the Laura and John Arnold Foundation asked the National Academy of Sciences to undertake an assessment of the scientific research on eyewitness identification and offer recommendations to improve eyewitness performance. The appointed committee issued its report, Identifying the Culprit: Assessing Eyewitness Identification, in 2014. In order to stimulate new and innovative research on statistical tools and the interrelationships between system and estimator variables, the Arnold Foundation in 2015 again called upon the National Academies. This report describes the development of the request for proposals, the processes followed by the committee as it evaluated the proposals, and the committee2019s assessment of the scientific merit and research design of the proposals.

Review of the Scientific Approaches Used During the FBI's Investigation of the 2001 Anthrax Letters - National Research Council (The National Academies Press, 2011)
Less than a month after the September 11, 2001 attacks, letters containing spores of anthrax bacteria (Bacillus anthracis, or B. anthracis) were sent through the U.S. mail. Between October 4 and November 20, 2001, 22 individuals developed anthrax; 5 of the cases were fatal. During its investigation of the anthrax mailings, the FBI worked with other federal agencies to coordinate and conduct scientific analyses of the anthrax letter spore powders, environmental samples, clinical samples, and samples collected from laboratories that might have been the source of the letter-associated spores. The agency relied on external experts, including some who had developed tests to differentiate among strains of B. anthracis. In 2008, seven years into the investigation, the FBI asked the National Research Council (NRC) of the National Academy of Sciences (NAS) to conduct an independent review of the scientific approaches used during the investigation of the 2001 B. anthracis mailings. Review of the Scientific Approaches Used During the FBI's Investigation of the Anthrax Letters evaluates the scientific foundation for the techniques used by the FBI to determine whether these techniques met appropriate standards for scientific reliability and for use in forensic validation, and whether the FBI reached appropriate scientific conclusions from its use of these techniques. This report reviews and assesses scientific evidence considered in connection with the 2001 Bacillus anthracis mailings.

Safe Science: Promoting a Culture of Safety in Academic Chemical Research - National Research Council (The National Academies Press, 2014)
Recent serious and sometimes fatal accidents in chemical research laboratories at United States universities have driven government agencies, professional societies, industries, and universities themselves to examine the culture of safety in research laboratories. These incidents have triggered a broader discussion of how serious incidents can be prevented in the future and how best to train researchers and emergency personnel to respond appropriately when incidents do occur. As the priority placed on safety increases, many institutions have expressed a desire to go beyond simple compliance with regulations to work toward fostering a strong, positive safety culture: affirming a constant commitment to safety throughout their institutions, while integrating safety as an essential element in the daily work of laboratory researchers. Safe Science takes on this challenge. This report examines the culture of safety in research institutions and makes recommendations for university leadership, laboratory researchers, and environmental health and safety professionals to support safety as a core value of their institutions. The report discusses ways to fulfill that commitment through prioritizing funding for safety equipment and training, as well as making safety an ongoing operational priority. A strong, positive safety culture arises not because of a set of rules but because of a constant commitment to safety throughout an organization. Such a culture supports the free exchange of safety information, emphasizes learning and improvement, and assigns greater importance to solving problems than to placing blame. High importance is assigned to safety at all times, not just when it is convenient or does not threaten personal or institutional productivity goals. Safe Science will be a guide to make the changes needed at all levels to protect students, researchers, and staff.

A Review of the FBI's Trilogy Information Technology Modernization Program - National Research Council (The National Academies Press, 2004)
The Federal Bureau of Investigation (FBI) is in the process of developing a modern information technology (IT) system2014the Trilogy program2014 that is designed to provide a high-speed network, modern workstations and software, and an application2014the Virtual Case File (VCF)2014to enhance the ability of agents to organize, access, and analyze information. Implementation of this system has encountered substantial difficulties, however, and has been the subject of much investigation and congressional concern. To help address these problems, the FBI asked the National Research Council (NRC) to undertake a quick review of the program and the progress that has been made to date. This report presents that review. The current status of four major aspects of the program2014the enterprise architecture, system design, program management, and human resources2014are discussed, and recommendations are presented to address the problems.

A Review of the DOE Plan for U.S. Fusion Community Participation in the ITER Program - National Research Council (The National Academies Press, 2009)
ITER presents the United States and its international partners with the opportunity to explore new and exciting frontiers of plasma science while bringing the promise of fusion energy closer to reality. The ITER project has garnered the commitment and will draw on the scientific potential of seven international partners, China, the European Union, India, Japan, the Republic of Korea, Russia, and the United States, countries that represent more than half of the world's population. The success of ITER will depend on each partner's ability to fully engage itself in the scientific and technological challenges posed by advancing our understanding of fusion. In this book, the National Research Council assesses the current U.S. Department of Energy (DOE) plan for U.S. fusion community participation in ITER, evaluates the plan's elements, and recommends appropriate goals, procedures, and metrics for consideration in the future development of the plan.

Promoting Chemical Laboratory Safety and Security in Developing Countries - National Research Council (The National Academies Press, 2010)
There is growing concern about the possible use of toxic industrial chemicals or other hazardous chemicals by those seeking to perpetrate acts of terrorism. The U.S. Chemical Security Engagement Program (CSP), funded by the U.S. Department of State and run by Sandia National Laboratories, seeks to develop and facilitate cooperative international activities that promote best practices in chemical security and safe management of toxic chemicals, including: Partnering with host governments, chemical professionals, and industry to assess and fill gaps in chemical security abroad. Providing technical expertise and training to improve best practices in security and safety among chemical professionals and industry. Increasing transparency and accountability for dangerous chemical materials, expertise, and technologies. Providing opportunities for collaboration with the international professional chemical community. The Department of State called on the National Academies to assist in the CSP's efforts to promote chemical safety and security in developing countries.

Evaluation of Demonstration Test Results of Alternative Technologies for Demilitarization of Assembled Chemical Weapons: A Supplemental Review for Demonstration II - National Research Council (The National Academies Press, 2001)
By direction of Congress, the U.S. Department of Defense's (DoD's) program manager for the Assembled Chemical Weapons Assessment (PMACWA) asked the National Research Council (NRC) Committee on Review and Evaluation of Alternative Technologies for Demilitarization of Assembled Chemical Weapons: Phase II (the ACW II committee) to conduct an independent scientific and technical assessment of three alternative technologies (referred to as Demo II) under consideration for the destruction of assembled chemical weapons at U.S. chemical weapons storage sites. The three technologies are AEA Technologies Corporation's (AEA's) electrochemical oxidation process; the transpiring-wall supercritical water oxidation and gasphase chemical reduction processes of Foster Wheeler\/Eco Logic\/Kvaerner (FW\/EL\/K); and Teledyne-Commodore's solvated electron process. Each of these technologies represents an alternative to incineration for the complete destruction of chemical agents and associated energetic materials. The demonstration tests were approved by the PMACWA after an initial assessment of each technology. The results of that initial assessment were reviewed by an earlier NRC committee, the Committee on Review and Evaluation of Alternative Technologies for Demilitarization of Assembled Chemical Weapons (the ACW I committee). For the present review, the committee conducted an indepth examination of each technology provider's data, analyses, and demonstration test results for the critical components tested. This review report supplements the ACW I report and considers the demonstration performance of the Demo II candidate technologies and their readiness for advancement to pilot-scale implementation. Because testing in these areas is ongoing, the committee decided to cut short its fact-finding efforts for input to this report as of March 30, 2001.

Evaluation of Demonstration Test Results of Alternative Technologies for Demilitarization of Assembled Chemical Weapons: A Supplemental Review - National Research Council (The National Academies Press, 2000)
In 1996, the U.S. Congress enacted two laws, Public Law 104-201 (authorization legislation) and Public Law 104-208 (appropriation legislation), mandating that the U.S. Department of Defense (DOD) conduct an assessment of alternative technologies to the baseline incineration process for the demilitarization of assembled chemical munitions. The PMACWA had previously requested that the National Research Council (NRC) perform and publish an independent evaluation of the seven technologies packages that had been selected during earlier phases of the Assembled Chemical Weapons Assessment (ACWA) program and deliver a report by September 1, 1999. However, to meet that deadline, the NRC Committee on Review and Evaluation of Alternative Technologies for Demilitarization of Assembled Chemical Weapons (ACW Committee) had to terminate its data-gathering activities on March 15, 1999, prior to the completion of demonstration tests. In September 1999, the PMACWA requested that the ACW Committee examine the reports of the demonstration tests and determine if the results changed the committee's original findings, recommendations, and comments. Evaluation of Demonstration Test Results of Alternative Technologies for Demilitarization of Assembled Chemical Weapons documents the committee's reassessment of the findings and recommendations in the original report, Review and Evaluation of Alternative Technologies for Demilitarization of Assembled Chemical Weapons.

A View of Global S&T Based on Activities of the Board on Global Science and Technology: Letter Report - National Research Council (The National Academies Press, 2011)
This letter report describes the 2009-2011 activities of the Board on Global Science and Technology (BGST) and provides an initial characterization of the global science and technology landscape that the Board can use as a roadmap to develop future activities. BGST met five times between November 2009 and May 2011. Board meetings were devoted to (1) identifying national security implications of the globalization of S&T, (2) building a baseline understanding of current indicators for the U.S. posture with regard to the evolving global S&T landscape, and (3) developing a BGST engagement strategy. The letter portion of the report summarizes activities of the board in its first year, and also describes some existing approaches to identifying and\/or benchmarking emerging technologies globally. It is followed by 5 appendixes which include three experimental examples of a qualitative approach to benchmarking, and brief descriptions of programs that are part of the National Academies complex, with which BGST has cooperated.

Review of Secondary Waste Disposal Planning for the Blue Grass and Pueblo Chemical Agent Destruction Pilot Plants - National Research Council (The National Academies Press, 2008)
The U.S. Army Program Manager for Assembled Chemical Weapons Alternatives (PMACWA) is charged with disposing of chemical weapons as stored at two sites: Pueblo, Colorado, and Blue Grass, Kentucky. In accordance with congressional mandates, technologies other than incineration are to be used if they are as safe and as cost effective. The weapons are to be disposed of in compliance with the Chemical Weapons Convention. Although an element of the U.S. Army, the PMACWA is responsible to the Assistant Secretary of Defense for Acquisitions, Technology, and Logistics for completing this mission. This book deals with the expected significant quantities of secondary wastes that will be generated during operations of the facilities and their closure. While there are only estimates for the waste quantities that will be generated, they provide a good basis for planning and developing alternatives for waste disposal while the plants are still in the design phase. Establishing efficient disposal options for the secondary wastes can enable more timely and cost-effective operation and closure of the facilities.

Chemical Dynamics: A Current Review (The National Academies Press, 1966)

National Transonic Facility: A Review of the Operational Plan (The National Academies Press, 1980)

Nuclear Chemistry: A Current Review (The National Academies Press, 1966)

Theoretical Chemistry: A Current Review (The National Academies Press, 1966)

Chemical Structure Information Handling: A Review of the Literature, 1962-1968 (The National Academies Press, 1969)

Source Material for Radiochemistry: 1965 Revision (The National Academies Press, 1965)

Source Material for Radiochemistry: 1970 Revision (The National Academies Press, 1970)

Radiochemistry of Mercury - National Research Council (The National Academies Press, 1970)